Analysis of Chronic Mild Stress-Induced Hypothalamic Proteome: Identification of Protein Dysregulations Associated With Vulnerability and Resiliency to Depression or Anxiety - Gong, Weibo; Liao, Wei; Fang, Chui; Liu, Yanchen; Xie, Hong; Yi, Faping; Huang, Rongzhong; Wang, Lixiang; Zhou, Jian (Frontiers in Molecular Neuroscience, 2021)
Chronic stress as a known risk factor leads to hyperactivity of the hypothalamus-pituitary-adrenal (HPA) axis in both depression and anxiety. However, the stress-induced dysfunction of the HPA axis in these disorders especially the common and unique molecular dysregulations have not been well-explored. Previously, we utilized a chronic mild stress (CMS) paradigm to segregate and gain depression-susceptible, anxiety-susceptible, and insusceptible groups. In this study, we continue to examine the possible protein expression alterations of the hypothalamus as the center of the HPA axis in these three groups by using a proteomic approach. Though isobaric tags for relative and absolute quantitation (iTRAQ)-based quantitative analysis, a total of 593 dysregulated proteins were identified. These were potentially associated with vulnerability and adaptability of CMS-caused depression or anxiety and therefore might become novel investigative protein targets. Further independent analysis using parallel reaction monitoring (PRM) indicated that 5, 7, and 21 dysregulated proteins were specifically associated with depression-susceptible, anxiety-susceptible, and insusceptible groups, respectively, suggesting that the same CMS differently affected the regulation system of the rat hypothalamic proteome. In summary, the current proteomic research on the hypothalamus provided insights into the specific and common molecular basis for the HPA dysfunction mechanisms that underlie resiliency and vulnerability to stress-induced depression or anxiety.